Simultaneous detection of Neisseria meningitidis, Haemophilus influenzae and Streptococcus sp. by polymerase chain reaction for the diagnosis of bacterial meningits Detecção simultânea da Neisseria meningitidis, Haemophilus influenzae e Streptococcus sp. pela reação em cadeia da polimerase no diagnóstico das meningites bacterianas - Luciane Failace; Mario Wagner; Marisa Chesky; Rosana Scalco; Luiz Fernando Jobim (Arquivos de Neuro-Psiquiatria)
The simultaneous detection of Neisseria meningitidis, Haemophilus influenzae, and Streptococcus sp. was assessed by polymerase chain reaction (PCR) for the diagnosis of bacterial meningitis, as well as the applicability of PCR as a routine test. A cohort study was carried out with 182 children (2 months to 12 years of age) with suspicion of bacterial meningitis. Routine tests identified the etiologic agent in 65/84 children whose clinical status and laboratory findings suggested the presence of bacterial meningitis. Bacterial meningitis was ruled out in 98 children. In 19 children, the etiologic diagnosis was not possible using standard methods; in 14 of these patients, the etiologic agent was identified by PCR (N. meningitidis=12; H. influenzae=1; Streptococcus sp.=1). The sensitivity of PCR was 88.1%; specificity, 99.0%; positive predictive value, 98.7%; and negative predictive, 90.1%. PCR is a useful complementary diagnostic technique, especially when Gram stain, culture, or antigenic detection are negative or inconclusive. Avaliamos o desempenho da reação em cadeia da polimerase (PCR) para detecção simultânea da Neisseria meningitidis, Haemophilus influenzae e Streptococcus sp. no diagnóstico das meningites bacterianas e sua aplicabilidade na rotina diagnóstica. Foi realizado um estudo de coorte com 182 crianças apresentando suspeita de meningite bacteriana. Em 84, havia alterações clínicas e laboratoriais sugestivas de meningite bacteriana. Destas, 65 tiveram o agente etiológico identificado pelos métodos laboratoriais de rotina e 19 ficaram sem diagnóstico etiológico. Em 98 pacientes foi excluído o diagnóstico de meningite bacteriana. Analisando o desempenho da PCR encontramos sensibilidade de 88,1%, especificidade de 99,0% e valores preditivos positivo e negativo de 98,7% e 90,1% respectivamente. Nos 19 pacientes com meningite bacteriana mas sem diagnóstico etiológico a PCR detectou microrganismos em 14, sendo 12 N. meningitidis, um H. influenzae e um Streptococcus sp. A PCR possui o potencial de poder aumentar os índices de identificação das técnicas tradicionais, principalmente nas situações onde a microscopia direta, cultura ou identificação antigênica são negativos ou inconclusivos.